Sistem Informasi Penggajian Karyawan Berbasis Web (Studi Kasus PT. Bridgestone Kalimantan Plantation) - Bagus Prasetyo; Afian Syafaadi Rizki; Dwi Agung Wibowo; Nina Mia Aristi; M. Najamudin Ridha (J-INTECH ( Journal of Information and Technology), 2024)
Bridgestone Kalimantan Plantation, a rubber plantation company, currently manages employee payroll semi-manually using a Delphi-based desktop application and Microsoft Excel. This approach encounters several challenges, such as limited accessibility, data integrity issues, and time-consuming processes. To address these problems, this study aims to develop a web-based payroll information system. The primary objective of this research is to improve accessibility, streamline payroll management processes, and enhance data accuracy and security. The system is designed using the Laravel framework, chosen for its ease of use and security in implementing authentication and authorization, as well as its future integration capabilities. The results of the study indicate that the developed system functions as needed, providing a more efficient platform, reducing errors, and improving the user experience for employees involved in the payroll process. The implementation of this system is expected to enhance the overall operational efficiency of PT. Bridgestone Kalimantan Plantation.